National Income Statistics - Planning Commission (Planning Commission, 1961)
The estimates of gross capital formation presented here include both fixed capital formation and change in stocks for the Indian economy during 1948—49 to 1960—61. separate presentation of gross fixed capital formation by type of capital goods and of gross capital formation by type of purchasers has also been attempted. Because of the highly tentative character of the estimates of depreciation, the estimates of net capital formation have been relegated to on appendix (Appendix1.1).
Central Statistical Organisation Department of Statistic
Central Statistical Organisation Department of Statistic